ANALYSIS OF SMAW IN DIFFERENT MATERIALS WITH ELECTRODE VARIATIONS - Rajab, Dede Ardi; Artitana, Lapi; Suprayitno, Agus (Department of Mechanical Engineering Education, 2023)
Welding is a technique for joining metals by melting part of the parent metal and filler metal with or without additional metal and producing a continuous connection. One type of welding that is often used is SMAW welding (Shield Metal Arc Welding). In SMAW welding, the influence of the electrode strength or amperage used plays an important role in welding, because it influences the results of the joint strength during welding. Therefore, the current setting must be appropriate to the material and choosing the right welding parameters will also improve the quality of the welding results. This research was conducted to determine the mechanical properties of tensile testing and the microstructure of the influence of the different electrodes and amperes that will be used. In this research, current variations of 70 A, 80 A, and 90 A were used and the types of electrodes used were E6013, E309-16 and E7018. The research results obtained from the tensile test had an optimum value for the E7018 electrode, 90 A with a tensile strength of 41 .60 kg/mm. The tensile test results for E7018 obtained an average tensile value of 33.19 kg/mm. The tensile test result value of E6013, 80 ampere has a value of 36.55 kg/mm, after being averaged the tensile strength of E6013 is 35.36 kg/mm, the tensile test result of E309, 80 A has a value of 38.15 kg/mm after being averaged got a tensile test value of 36.20 kg/mm.